"Literature is the best antidote to fundamentalism": Tabish Khair in conversation with Goutam Karmakar. Issue 2 (4th March 2019) - Karmakar, Goutam
ABSTRACT: In this wide-ranging interview conducted in 2018, the award-winning poet, novelist, journalist and academic Tabish Khair discusses his early poetry and his recent fiction, as well as his critical writings. In the process, he talks about literature, representation, immigration, home, cosmopolitanism, and the culture of small towns, as well as more overtly political matters such as Islamophobia and Islamic fundamentalism. In particular, Khair insists on a complex reading of migration and alienation, and of the role of literature in combating fundamentalism. He discusses the notion of identity as a construct, and argues that migration should not be automatically associated with alienation or loneliness. While noting and criticizing the incidence of Islamophobia, Khair insists, perhaps controversially, on the need for religious Muslims to re-examine their assumptions about themselves, their world and others.